Evaluating the ion exchange chromatography for matrix‐assisted PEGylation and purification of consensus interferon. (3rd November 2019) - Bajwa, Fakiha; Ahmed, Nadeem; Khan, Mohsin Ahmad; Azam, Farhana; Akram, Muhammad; Tahir, Saad; Zafar, Ahmad Usman
Abstract: Scientists have implemented protein‐PEGylation technology for boosting‐up the pharmacokinetics and stability of recombinant therapeutic proteins. In the present study, (a) matrix‐assisted PEGylation was compared with solution‐phase PEGylation and (b) matrix‐assisted PEGylation was performed with different ion exchange resins for impact of chromatography medium on yield and purity of PEGylated product. DEAE Sepharose CL 6B, DEAE Fracto gel, and Macro cap Q ion exchange chromatography medium were compared for on column PEGylation and purification of cIFN. A MSC‐PEG of 12.0 KDa was selected. cIFN was bound to ion exchange medium, and PEG solution was passed through resin for 180 Min, and protein was eluted by sodium chloride linear gradient. Yield and purity for mono‐PEGylated cIFN with Macro cap Q matrix was 75% and 99%, respectively, whereas for DEAE Sepharose was 45% and 60%. DEAE Fracto gel TM purity was 85% with 50% yield of mono‐PEGylated cIFN. Further investigation of in vitro biological activities demonstrated that about 30% antiviral activity was reduced as compared to unmodified cIFN. However, thermal stability was significantly improved. The present study proved that matrix‐assisted PEGylation can improve the yield and purity of mono‐PEGylated product, and Macro Cap resin provided the highest yield of a homogeneous product. In present study, (a) matrix‐assisted PEGylation was compared with solution‐phase PEGylation and (b) matrix‐assisted PEGylation was performed with different ion exchange resins for impact of chromatography medium on yield and purity of PEGylated product. Matrix‐assisted PEGylation increases the yield of mono‐PEGylated product and further Macro Cap TM produced highest yield and purity of PEGylated cIFN.